ANALISIS PEMIKIRAN TENGKU AMIR HAMZAH TENTANG PENDIDIKAN KULTURAL MELAYU DI KABUPATEN LANGKAT - Muhammad Muklis; Muhammad Saleh (STAI Jama'iyah Mahmudiyah Tanjung Pura, 2024)
This study departs from the researcher's observation of a small town that is Tanjung pura Langkat Regency by looking at the history of Tengku Amir Hamzah which is still known so far in terms of culture and education but here researchers will review more in terms of cultural education of Malay culture in Langkat. This research focuses on the thought of Tengku Amir Hamzah about Malay cultural education in Langkat to the people of Langkat who are in the process of education using literary works as a medium of learning that is still preserved. The type of research is qualitative research, data collection methods by means of observation, interviews, and documentation. Data analysis techniques with inductive analysis to find research results. Malay cultural education until now there are still preserving with some variations. From the thoughts of Tengku Amir Hamzah, we can know that Malay culture upholds good manners. No wonder from several sources many say that Tengku Amir Hamzah is a very good figure in speech. Amir Hamzah is a creative figure in creating his works. He is an explorative poet who has cultural and aesthetic